(untitled) (Società e diritti, 2024)
Given the complexity and pluralism that mark contemporary legal experience, the principle of certainty is riconsidered in the context of the crisis of the legal case and the construction of the relationship between case and rule. On the basis of hermeneutics as a general legal theory, the semantics of complexity and pluralism shows how it is possible to find in the activity of the jurist a resource for reflecting on both the work of positivation and the canons controlling legal decision-making. The result is an internal and external view of the two meanings, that allows us to think pluralism and complexity of the social and legal reasons that legitimise and problematise the rule’s position in interpretation and argumentation.